Deciphering the Therapeutic Potential of Novel Pentyloxyamide-Based Class I, IIb HDAC Inhibitors against Therapy-Resistant Leukemia - Fischer, Fabian; Schliehe-Diecks, Julian; Tu, Jia Wey; Gangnus, Tanja; Ho, Yu Lin; Hebeis, Mara; Alves Avelar, Leandro A.; Scharov, Katerina; Watrin, Titus; Kemkes, Marie; Stachura, Pawel; Daugs, Katharina; et al. (Journal of Medicinal Chemistry, 2024)
Histone deacetylase inhibitors (HDACi) are established anticancer drugs, especially in hematological cancers. This study aimed to design, synthesize, and evaluate a set of HDACi featuring a pentyloxyamide connecting unit linker region and substituted phenylthiazole cap groups. A structural optimization program yielded HDACi with nanomolar inhibitory activity against histone deacetylase class I/IIb enzymes. The novel inhibitors (4d and 4m) showed superior antileukemic activity compared to several approved HDACi. Furthermore, 4d and 4m displayed synergistic activity when combined with chemotherapeutics, decitabine, and clofarabine. In vitro pharmacokinetic studies showed the most promising profile for 4d with intermediate microsomal stability, excellent plasma stability, and concentration-independent plasma protein binding. Additionally, 4d demonstrated comparable in vivo pharmacokinetics to vorinostat. When administered in vivo, 4d effectively inhibited the proliferation of leukemia cells without causing toxicity. Furthermore, the binding modes of 4d and 4m to the catalytic domain 2 of HDAC6 from Danio rerio were determined by X-ray crystallography.
CRIS-Team Scopus Importer:2024-12-06